Termophilic fungal communities in soils and litter of forest reservation of Vár-hegy - Kósa-Kovács, Míra; Sebők, Flóra; Szoboszlay, Sándor; Kriszt, Balázs; Dobolyi, Csaba (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
The soils of three forest sites were examined by quantitative microbiological culturing, with the use of four mycological media at 50°C. From the soil of the association Quercetum petraeae-cerris and Carici pilosae Carpinetum we pointed out 102-103 CFU/g fungal elements. In the rendzina soil of Cotineto-quercetum pubescentis requiring warmer climate, according to our investigations, 103-104 CFU/g thermophilic fungi live. Rhizomucor pusillus, Thermomyces lanuginosus and Myceliophthora thermophila occurred as the most common species. The populations of thermophilic fungi showed a definite seasonality in soils of the different forest sites. The residual parts of different herbaceous and arboreal plants were colonised by several thermophilic fungal species. Incubating them in wet chamber we obtained nine thermophilic species on the surface of twigs. The most common species belonging to different taxons were Rhizomucor miehei, Chaetomium thermophilum and Thermomyces lanuginosus. We made axenic cultures into a culture collection for further investigations.
Keywords: fungal communities; forest reservation; thermophilic fungi; soil fungi